Birokrasi Pemerintahan dan Pelayanan Publik Adaptive dalam Bingkai Keistimewaan Daerah Istimewa Yogyakarta - Nugroho, Dwinanta; Subagio, Hani; Rachmadi, Hari (Metta : Jurnal Ilmu Multidisiplin, 2023)
The public's main complaint about public services provided by government officials is that they often do not comply with established procedures, even though there are minimum service standards. This problem highlights the challenges in government implementation. This research discusses efforts to reconstruct government bureaucracy and public services in the context of moving towards Yogyakarta's privileges. This research method is normative juridical by exploring the legal norms that regulate the government sector and public services in the Special Region of Yogyakarta. Research involves identifying relevant legal sources, which include laws, government regulations, and constitutional documents which are then related to bureaucracy and public services. Next, an in-depth analysis of the content of these legal norms was carried out, with a focus on compliance and conformity with the concept of Yogyakarta exceptionalism. This research also carries out comparisons between various legal norms, looking for any inconsistencies that may exist. The research results revealed several key findings. First, it was found that several legal norms needed to be revised or updated to better support the unique vision of Yogyakarta, especially in relation to reform in the bureaucracy and improvements to public services. Second, this research builds a good basis for understanding potential conflicts or obstacles that may arise in the implementation of bureaucratic reconstruction and public services in Yogyakarta. Based on these findings, this research provides recommendations to the government and relevant stakeholders to take concrete steps to support efforts towards making Yogyakarta unique. These recommendations involve policy updates, increased coordination between government agencies, and improved communication with the public. This article makes an important contribution in the context of understanding law and policy related to the reconstruction of bureaucracy and public services in Yogyakarta, as well as its relevance to the vision of Yogyakarta's special features.